Pregnancy outcomes in twin pregnancies over 10 years - Junghyun Jee; Su Jung Hong; Sungyeon Ha; Ho Yeon Kim; Ki Hoon Ahn; Soon-Cheol Hong; Min-Jeong Oh; Hai-Joong Kim; Geum Joon Cho (Korean Society of Obstetrics and Gynecology, 2023)
Objective The aim of this study was to evaluate the changes in twin pregnancy outcomes between 2007 and 2016 in a Korean population. Methods The data for this nationwide population-based study was obtained from the national birth registry of the Korean National Statistical Office and the Health Insurance Review & Assessment Service of Korea. Women with twin pregnancies who gave birth between 2007 and 2016 were included. Results From 2007 to 2016, the rate of twin pregnancies increased (1.37% vs. 1.91%, respectively, P<0.0001). The risk of preterm birth (adjusted odds ratio [aOR], 1.77; 95% confidence interval [CI], 1.66-1.89) also increased; however, the risk of twin growth discordance (aOR, 0.90; 95% CI, 0.82-0.99) decreased. The risks of cesarean section (aOR, 1.16; 95% CI, 1.03-1.29), gestational diabetes mellitus (aOR, 2.10; 95% CI, 1.83-2.39), and postpartum hemorrhage (aOR, 1.27; 95% CI, 1.14-1.41) all increased from 2007 to 2016. Conclusion Twin pregnancy outcomes have changed significantly in Korea over a recent 10-year period.